China at the crossroads: the economics of tobacco and health. (24th May 2006) - Hu, T-W; Mao, Z; Ong, M; Tong, E; Tao, M; Jiang, H; Hammond, K; Smith, K R; de Beyer, J; Yurekli, A
Abstract : Objective: To analyse economic aspects of tobacco control policy issues in China. Methods: Published and collected survey data were used to analyse economic consequences of smoking. Economic analysis was used to address the role of tobacco farmers and the cigarette industry in the Chinese economy. Results: In the agricultural sector, tobacco has the lowest economic rate of return of all cash crops. At the same time, the tobacco industry's tax contribution to the central government has been declining. Conclusion: Economic gains become less important as the negative health impact of smoking on the population garners more awareness. China stands at a crossroads to implement the economic promises of the World Health Organization's Framework Convention on Tobacco Control and promote the health of its population.